Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
3/7 + 4/9 + 5/11 + 8/14 + 10/18 + 12/22
= 3/7 + 4/9 + 5/11 + 4/7 + 5/9 + 6/11
= ( 3/7 + 4/7 ) + ( 4/9 + 5/9 ) + ( 5/11 + 6/11 )
= 7/7 +9/9 + 11/11
= 1 + 1 + 1
= 3
tk mk nha , cảm ơn ạ , được ko á ?????????
3/7 + 4/9 + 5/11 + 8/14 + 10/18 + 12/22 = 3
-3/11.(-22)/66.121/15
=(-3).(-22).121
11.66.15
=11
15
3/7.2/5.7/3.20.19/72
=3.2.7.20.19
7.5.3.72
=76
16
6/7.8/13+6/13.9/7-3/13.6/7
=6/7.8/13+6/7.9/13-3/13.6/7
=6/7.(8/13+9/13-3/13)
=6/7.14/13
=12/13
-1/4.152/11+68/4.(-1)/11
=152/4.(-1)/11+68/4.(-1)/11
=(-1)/11.(152/4+68/4)
=(-1)/11.220/4
=-110/22
-5/7.2/11+(-5)/7.9/11+12/7
=-5/7.2/11+-5/7.9/11+12/7
=-5/7.(2/11+9/11)+12/7
=-5/7.1+12/7
=(-5)/7+12/7
=7/7
=1
146/13-(18/7+68/13)
=146/13-18/7-68/13
=(146/13-68/13)-18/7
=78/13-18/7
=6-18/7
=42/7-18/7
=24/7
\(\dfrac{7}{22}:\dfrac{3}{11}+\dfrac{7}{22}:\dfrac{4}{11}=\dfrac{7}{22}.\dfrac{11}{3}+\dfrac{7}{22}.\dfrac{11}{4}=\dfrac{7}{22}\left(\dfrac{11}{3}+\dfrac{11}{4}\right)=\dfrac{7}{22}.\dfrac{77}{12}=\dfrac{49}{24}\)
22/7 : ( 11 - x ) + 2/3 = 7/5
22/7 : ( 11 -x ) = 7/5 - 2/3
22/7 : ( 11 -x ) = 11/15
11-x = 22/7 : 11/15
11- x = 30/7
x = 11 - 30/7
x = 47/7
\(\frac{9}{8}-\frac{-11}{8}=\frac{9-\left(-11\right)}{8}=\frac{9+11}{8}=\frac{20}{8}=\frac{5}{2}\)
\(-\frac{1}{2}-\frac{5}{2}=\frac{-1-5}{2}=\frac{-6}{2}=-3\)
\(\frac{4}{3}-\frac{7}{3}=\frac{4-7}{3}=\frac{11}{3}\)
\(\frac{3}{-5}-\frac{-8}{10}=\frac{6}{-10}-\frac{-8}{10}=\frac{-6}{10}-\frac{-8}{10}=\frac{-6-\left(-8\right)}{10}=\frac{-6+8}{10}=\frac{2}{10}=\frac{1}{5}\)
\(\frac{5}{7}-\frac{-3}{21}=\frac{5}{7}-\frac{-1}{7}=\frac{5-\left(-1\right)}{7}=\frac{5+1}{7}=\frac{6}{7}\)
\(\frac{4}{-3}-\frac{9}{27}=\frac{4}{-3}-\frac{1}{3}=\frac{-4}{3}-\frac{1}{3}=\frac{-4-1}{3}=\frac{-5}{3}\)
\(\frac{7}{29}-\frac{9}{29}=\frac{7-9}{29}=\frac{2}{29}\)
\(\frac{-7}{22}-\frac{9}{22}=\frac{-7-9}{22}=\frac{-16}{22}=\frac{-8}{11}\)
\(\frac{-23}{7}-\frac{31}{7}=\frac{-23-31}{7}=\frac{-54}{7}\)
7\22 / 3\11 + 7\22 / 4 \11
=7\22 / (3\11 + 4\11)
=7\22 / 5/11
=..........
= 7\22 : ( 3\11 + 4\11)
= 7\22 : 7\11
= 7\22 x 11\7
= 1\2